CALCULATION OF LIGHTING INSTALLATIONS AND BUDGET COSTS ON ROAD PROTOCOLS (CASE STUDY JALAN MERDEKA – SUTOMO PEMANG SIANTAR) - Saragih, Jopinus; Bahmani Oskooee, Mohsen; Mayanta Tariga, Hendri; K Tarigan, Adrian; Setiawan, Ben (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
Based on the results of the discussion in data processing according to field data, the results of the discussion are as follows: The number of street light poles is 100 rods per trip and one hundred street lights. The distance between the poles is 50 meters and the height of the pole is 7 meters and the LED lights are 90 watts so they don't match the standard of street light lighting. The installation must comply with the provisions for installing aerial cables in PUIL 2000 TC (Twisset cable), the designation for aerial cables that are familiar in the field. (in PUIL various aerial cables NFY, NFAY, NF2X, NFA2X, etc.) On TC cables for identification: On TC cables there is a line / strip one is used to mark phase = N, On TC cables there is no line / strip used to mark neutral = N Nominal current on each panel is 12, 37 amperes and the total use of lighting on the Sutomo-Merdeka road is 18,000 watts. The total budget costs are; total material price + tax + profit = IDR 1,515,164,000.- + IDR 174,243,860.- + IDR 303,032,000.-, = IDR 1,992,440,660.-